Introduction to issue on Education for a tolerant and multicultural Indonesia - PARKER, Lyn (Institutional Knowledge at Singapore Management University, 2014)
Ethnic, religious and linguistic diversity is intrinsic to the concept of Indonesia. The national motto of Bhinneka Tunggal Ika, often translated as ‘Unity in Diversity’, though more directly translatable as ‘Diverse but One’, is emblazoned on the national symbol, the Garuda, which appears in classrooms, offices, statues and even living rooms all around the country. Indonesia has long enjoyed the reputation of a diverse and tolerant country. However, after the fall of Suharto in May 1998, it seemed to erupt in a conflagration of violence. Religious and ethnic conflicts alerted both citizens and scholars of Indonesia to the danger of disintegration, and the nation’s famed tolerance appeared fragile.